Atrophic meibomian gland dysfunction induced by eyelid margin cryotherapy with liquid nitrogen - Shu Wang; Yulin Li; Jingfan Gao; Jia Lin; Xin Jin; Hong Zhang (Scientific Reports)
Abstract To develop an atrophic Meibomian Gland Dysfunction (MGD) animal model via liquid nitrogen cryotherapy, the eyelid edges of C57 mice exposure to liquid nitrogen for 30 s. Morphology of MG and ocular surface were assessed using stereomicroscopy and a slit lamp microscope at multiple time points post-injury. Acinar loss and atrophy were observed from day 7, with increased inflammation and apoptosis, and decreased proliferation in acinar cells. Corneal epithelial defects appeared after day 14. Liquid nitrogen induced selective damage to meibomian acinar cells, simulating MGD pathology effectively, with peak effects at day 21, providing a relevant model for atrophic MGD research.